2014
DOI: 10.1007/s10551-014-2347-9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cognitive Determinants of Consumers’ Support for the Fair Trade Movement

Abstract: Despite the reasonable explanatory power of existing models of consumers' ethical decision making, a large part of the process remains unexplained. This article draws on previous research and proposes an integrated model that includes measures of the theory of planned behavior, personal norms, self-identity, neutralization, past experience, and attitudinal ambivalence. We postulate and test a variety of direct and moderating effects in the context of a large survey with a representative sample of the U.K. popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 87 publications
6
72
1
3
Order By: Relevance
“…Fair trade has also become the most common context in which to study ethical consumption in the last decade making our findings comparable to existing literature (Andorfer and Liebe 2012; Carrington et al 2010;Chatzidakis et al 2015). …”
Section: Sample Selectionsupporting
confidence: 87%
“…Fair trade has also become the most common context in which to study ethical consumption in the last decade making our findings comparable to existing literature (Andorfer and Liebe 2012; Carrington et al 2010;Chatzidakis et al 2015). …”
Section: Sample Selectionsupporting
confidence: 87%
“…Also, Armitage and Conner (2001) admit that 80% of the behaviour remains unexplained by Ajzen's theory. In the empirical studies identified (Auger & Devinney, 2007;Chatzidakis et al, 2014;Chatzidakis et al, 2006), attitude-behaviour gap requires therefore a more holistic approach, considering the complexity of the determinants affecting and hindering pro-environmental behaviour.…”
Section: Key Determinants Of Ethical Decision Makingmentioning
confidence: 99%
“…Since these items capture the common denominator of justifiability for the neutralization construct regardless of the type of excuses used, they should suffice for the purpose of this study. From a practical perspective, measures of Chatzidakis et al () also have the advantage of simplifying the survey considerably for the respondents given the many measurement items included in this research. The full list of items is provided in Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…For me, not complying with the organizational information security policies and procedures is justifiable. Chatzidakis et al (2016) 2. I have many arguments against complying with the Work ethical climate:…”
Section: Supporting Informationmentioning
confidence: 99%